Changes in the structural and mechanical properties of bakery products with the addition of buckwheat bran - Shevchenko, Anastasiia (My University, 2021)
In the paper the influence of dietary fiber of buckwheat as a product for dietary nutrition, on structural and mechanical properties of dough with fructose for diabetic bakery products was studied. Structural and mechanical properties of dough were characterized by a farinograph and an alveograph. The water absorbing capacity of bran was determined by centrifugation, the size of bran – by laboratory sieving.
Keywords: fiber; buckwheat; cellulose; fructose; bakery product; кафедра технології хлібопекарських і кондитерських виробів